Litter Deposition and Nitrogen Return in Rotationally Stocked Smooth Bromegrass Pastures. (1st January 2014) - Guretzky, John A.; Schacht, Walter H.; Wingeyer, AnaB.; Klopfenstein, Terry J.; Watson, Andrea
Abstract : Understanding how management systems impact nutrient cycling is important to pasture sustainability. From 2010 to 2011, we investigated how supplementation of beef cattle ( Bos taurus ) with corn ( Zea mays L.) dried distillers grains plus solubles (DDGS) on unfertilized, rotationally stocked smooth bromegrass ( Bromus inermis Leyss.) pasture (SUPP) affected the litter pool, residual herbage mass, litter deposition, and litter quality relative to unsupplemented beef cattle rotationally stocked on unfertilized control (CONT) and N‐fertilized (FERT) smooth bromegrass pastures. As hypothesized based on management for greater herbage mass and animal demand during the grazing season, litter deposition was 48% greater in FERT than CONT and SUPP. Management effects, however, depended on year and rotation. Differences in the litter pool, residual herbage mass, and litter deposition typically were greatest before and after the third and fourth rotations, time periods coinciding with peak herbage mass. Meanwhile, deposited litter contained 16.5, 18.1, and 18.9 g N kg –1 and returned 27, 30, and 46 kg N ha –1 through the 158‐d grazing season, equivalent to 35, 23, and 34% of total N returning through litter and excreta in CONT, SUPP, and FERT, respectively. Trampling during the 4‐ to 6‐d grazing periods and senescence of herbage contributed to litter deposition. Increase of litter deposition and N return during the grazing season in FERT indicated this system may maintain better soil quality than CONT and SUPP. More research is necessary to examine how changes in litter deposition and N return affect litter decomposition, N losses, and soil organic matter dynamics.